Strategic management : total quality and global competition - Stahl, Michael J. (Blackwell, 1997)
Strategic management decisions for total quality and global competition. The environment and the strategic plan. International strategic decisions. Business ethics and corporate social responsibility. Corporate strategy. Business-level strategy: competitive strategy. Business-level strategy: total quality and customer value strategy. Functional strategy. Functional strategy. Strategy implementation: structure and teams. Strategy implementation: culture and behavior. Evaluation, control, and process improvement.